Chromatin Remodeling and Transcriptional Control in Innate Immunity: Emergence of Akirin2 as a Novel Player - Tartey, Sarang (Biomolecules, 2015)
Transcriptional regulation of inflammatory gene expression has been at the forefront of studies of innate immunity and is coordinately regulated by transcription factors, including NF-κB, and chromatin modifiers. The growing evidence for involvement of chromatin in the regulation of gene expression in innate immune cells, has uncovered an evolutionarily conserved role of microbial sensing and chromatin remodeling. Toll-like receptors and RIG-I-like receptors trigger these signaling pathways leading to transcriptional expression of a set of genes involved in inflammation. Tightly regulated control of this gene expression is a paramount, and often foremost, goal of most biological endeavors. In this review, we will discuss the recent progress about the molecular mechanisms governing control of pro-inflammatory gene expression by an evolutionarily conserved novel nuclear protein Akirin2 in macrophages and its emergence as an essential link between NF-κB and chromatin remodelers for transcriptional regulation.